A Computational Fluid‐Dynamics Assessment of the Improved Performance of Aerodynamic Rain Gauges. Issue 2 (3rd February 2018) - Colli, Matteo; Pollock, Michael; Stagnaro, Mattia; Lanza, Luca G.; Dutton, Mark; O'Connell, Enda
Abstract: The airflow surrounding any catching‐type rain gauge when impacted by wind is deformed by the presence of the gauge body, resulting in the acceleration of wind above the orifice of the gauge, which deflects raindrops and snowflakes away from the collector (the wind‐induced undercatch). The method of mounting a gauge with the collector at or below the level of the ground, or the use of windshields to mitigate this effect, is often not practicable. The physical shape of a gauge has a significant impact on its collection efficiency. In this study, we show that appropriate "aerodynamic" shapes are able to reduce the deformation of the airflow, which can reduce undercatch. We have employed computational fluid‐dynamic simulations to evaluate the time‐averaged airflow realized around "aerodynamic" rain gauge shapes when impacted by wind. Terms of comparison are provided by the results obtained for two standard "conventional" rain gauge shapes. The simulations have been run for different wind speeds and are based on a time‐averaged Reynolds‐Averaged Navier‐Stokes model. The shape of the aerodynamic gauges is shown to have a positive impact on the time‐averaged airflow patterns observed around the orifice compared to the conventional shapes. Furthermore, the turbulent air velocity fields for the aerodynamic shapes present "recirculating" structures, which may improve the particle‐catching capabilities of the gauge collector. Key Points: Atmospheric precipitation measurements Wind‐induced undercatch of precipitation gauges Computational fluid‐dynamics modeling